Case report: Pregnancy After Vitrification of Biopsied Human Blastocysts Previously Frozen by the Slow Method - M., Batwala; M., Wilding; T., Dalapati; G., Nargund (European Scientific Journal, ESJ, 2018)
Pre-implantation genetic screening (PGS) with trophectoderm biopsy is an extremely powerful technique for the determination of embryos with a high implantation potential. Patients with cryopreserved embryos seeking PGS have had limited access to this treatment due to the need to thaw, biopsy, and refreeze these embryos. This is especially true for patients with embryos cryopreserved by the slow freeze technique due to the low survival rate after thawing. In this case report, we describe the application of refreezing with the vitrification technique to embryos thawed with the slow technique and biopsied for PGS. The patient had a total of 8 blastocysts thawed, biopsied, and refrozen with vitrification. Next Generation Sequencing (NGS) of these embryos revealed that 4 blastocysts were euploid. The patients achieved a pregnancy on the the first frozen embryo transfer procedure that terminated after 11 days. The second frozen embryo transfer procedure resulted in the live birth of a 3800g boy, demonstrating that thaw, biopsy, and refreeze are applicable to human reproduction even in cases where embryos have been cryopreserved by the slow technique